The Role of Social Support and Self-efficacy for Planning Fruit and Vegetable Intake - Zhou, G.; Gan, Y.; Hamilton, Kyra; Schwarzer, R. (Elsevier Inc, 2017)
Objective: The aim of the current study was to examine the joint effect of self-efficacy, action planning, and received social support on fruit and vegetable intake. Design: The study used a longitudinal design with 3 waves of data collection. Setting: Major university campus in Beijing, China. Participants: Young adults (n = 286). Variables Measured: Age, gender, body mass index, dietary self-efficacy, and baseline behavior were measured at time 1. Two weeks after time 1, received social support and action planning were assessed (time 2); 4 weeks after time 1, subsequent fruit and vegetable consumption was measured (time 3). Analysis: In a path analysis, action planning at time 2 was specified as a mediator between self-efficacy at time 1 and fruit and vegetable intake at time 3, controlling for age, gender, body mass index, and baseline behavior. In addition, in a conditional process analysis, received social support at time 2 was specified as a moderator of the self-efficacy–planning relationship. Results: Action planning mediated between self-efficacy and subsequent dietary behavior, and received social support moderated between self-efficacy and planning supporting a compensation effect. Action planning served as a proximal predictor of fruit and vegetable intake, and planning one's consumption was facilitated by dietary self-efficacy. Conclusions and Implications: Through the identification of social cognitive factors influencing dietary planning, interventions can target self-efficacy and received social support to test the efficacy of these mechanisms in increasing individuals’ ability to ensure they consume adequate amounts of fruits and vegetables.